Maternal immunization efforts of the National Institutes of Health. Issue 47 (25th November 2015) - Rubin, Fran A.; Koso-Thomas, Marion; Isaacs, Maggie Brewinski; Piper, Jeanna; Read, Jennifer; Nesin, Mirjana
Abstract: Over the last 35 years, efforts at the National Institutes of Health (NIH) to protect mothers and their infants against infectious diseases have involved a bench-to-bedside approach. Basic and translational research that provided a foundation for clinical trials of vaccines in pregnancy include natural history and vaccine antigen identification studies. Development of laboratory assays and reagents have been funded by NIAID; these are critical for the advancement of vaccine candidates through the preclinical and clinical steps along the maternal immunization research pathway to support vaccine efficacy. Animal models of maternal immunization have been developed to evaluate efficacy of vaccine candidates. Clinical studies required development of maternal immunization protocols to address specific pregnancy related issues, for enrollment and safety assessment of mothers and their infants. NIH has organized and participated in meetings, workshops and other collaborative efforts with partners have advanced maternal immunization efforts. Partners have included many institutes and offices at NIH as well as other Department of Health and Human Services agencies and offices (Food and Drug Administration, Centers for Disease Control and Prevention, National Vaccine Program Office), World Health Organization, academic investigators, Biotech and pharmaceutical companies, and nonprofit organizations such as the Bill and Melinda Gates Foundation. These research and development partnership are essential for advancing maternal immunization. Continued efforts are needed to promote maternal immunization to protect pregnant women and their infants against vaccine-preventable infectious disease, especially in resource-limited settings where the burden of infections is high.